2019
DOI: 10.3390/su11164506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indoor Plants on Self-Reported Perceptions: A Systemic Review

Abstract: Bringslimark, Hartig, and Pati conducted a literature review of empirical studies investigating the psychological benefits of indoor plants, all of which adopted an experimental design and were written in English. However, the researchers did not follow the rigorous Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) protocol. Additionally, the reviewed data were obtained at least a decade ago, and thus require an update. Therefore, the present article reports a systemic review of the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 45 publications
3
34
0
Order By: Relevance
“…These results are of considerable importance for the extension of previous literature on health conditions in the living environment, such as the home and workplace ( Dreyer et al, 2018 ). For example, the presence of plants in working environments seems to reduce perceived stress and, in general, to promote positive emotions and reduce negative feelings ( Han, & Ruan, 2019 ). Interestingly, our results are inconsistent with those reporting associations between presence of indoor plants and lower level of anxiety ( Hassan et al, 2018 ; Toyoda et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are of considerable importance for the extension of previous literature on health conditions in the living environment, such as the home and workplace ( Dreyer et al, 2018 ). For example, the presence of plants in working environments seems to reduce perceived stress and, in general, to promote positive emotions and reduce negative feelings ( Han, & Ruan, 2019 ). Interestingly, our results are inconsistent with those reporting associations between presence of indoor plants and lower level of anxiety ( Hassan et al, 2018 ; Toyoda et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A second opportunity to engage with greenery at home is through indoor vegetation. Potted plants can reduce stress, physical discomfort, anxiety, and depressive symptoms ( Chang and Cheng 2005 ; Fjeld, 2000 ; Hall and Knuth, 2019 ; Han and Ruan, 2019 ) as well as increase attention ( Raanaas et al, 2011 ; Hall and Knuth, 2019 ; Kim et al, 2018 , 2020 ), mood ( Han and Ruan, 2019 ), and cognitive performance ( Adamson and Thatcher, 2019 ; Hall and Knuth, 2019 ). In one study, the mere presence of plants in the classroom also contributed to higher perceived restoration and positive affect of students ( Han and Ruan, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Potted plants can reduce stress, physical discomfort, anxiety, and depressive symptoms ( Chang and Cheng 2005 ; Fjeld, 2000 ; Hall and Knuth, 2019 ; Han and Ruan, 2019 ) as well as increase attention ( Raanaas et al, 2011 ; Hall and Knuth, 2019 ; Kim et al, 2018 , 2020 ), mood ( Han and Ruan, 2019 ), and cognitive performance ( Adamson and Thatcher, 2019 ; Hall and Knuth, 2019 ). In one study, the mere presence of plants in the classroom also contributed to higher perceived restoration and positive affect of students ( Han and Ruan, 2019 ). Another study found that students transplanting an indoor plant experienced reduced psychological and physiological stress and feelings of relaxation compared with working on a computer ( Lee et al, 2015b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As beneficial outcomes of contact with nature are known, several studies has given to showing the significance of the natural spaces for human prosperity [7,8,9]. Studies have come to promising conclusions on the psycho-physiological impacts of green spaces [10,11,12,13,14,15]. Conservation of green spaces, in terms of quantity and quality, is an urgent global challenge in the face of growing urbanization [16,17].…”
Section: Introductionmentioning
confidence: 99%